The Concept of Modern Asceticism According to Max Weber Perspective(Case Study of Asceticism and Its Implications in The Theological Study Program Of UKSW) - Prayogo, Tonny Ilham; Syamsul Hadi Untung; Nurmala Indah; Nailatu Lutfiyah Sidqi; Shofia Ristiana Rahman; Nabila Hafitzah; Yesi Ameilia Pramesti; Aqila Thifal Khansa (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2025)
Asceticism, which is often identified as the act of mortification, is an attempt by a Christian to achieve Christlike perfection. In this act of asceticism, they are willing to abandon worldly pleasures and continue to strive for perfection. Asceticism is often associated with monastic practices to evoke behaviors or attitudes such as maintaining speech, restraining the soul, lack of food, seclusion, and limiting needs. The philosophy of contemporary asceticism is more dominant than the application of Max Weber's theory. The purpose of Asceticism was used by Weber as a potential transformation toward the